Effects of age on quality of slaughterhouse by-products in Black Bengal goat (Bangladesh Journal of Animal Science, 2023)
This study was conducted with a view to investigate the yield percentage as well as nutritional composition of slaughterhouse by-products from Black Bengal goats of Bangladesh depending on different age groups. The experiment was conducted in different markets and slaughterhouses of Mymensingh district. Data and samples were collected from 50 (fifty) goats of different ages. Treatment group were executed according to the age, namely T0= 0 permanent incisor teeth (under 1 year), T1= 2 permanent incisor teeth (1 to 1.5 year), T2= 4 permanent incisor teeth (2 years), T3= 6 permanent incisor teeth (2 to 2.5 years), T4= 8 permanent incisor teeth (more than 2.5 years). Live weight, warm carcass weight, dressing percentage, percentage and nutritional composition of different slaughterhouse by-products were measured to identify the variation among the age group. The results showed a wide variation of yield percentage and nutritional composition of edible by-products for different ages of Black Bengal goats. A significant variation (P>0.01) of dressing percentage was found with the increase of age. Dressing percentage was 45.87 ± 3.23 in T0 group and 55.94 ± 2.08 in T4 group. Live weight and warm carcass weight were also increased significantly with the increase of age. No significant variation was found in the weight and percentage of different inedible by-products like skin, eye, teeth and hoof as well as edible by-products like liver, brain, kidney, lungs, heart, tongue, intestine with the increase of age. Higher percentage of dry matter and ether extract was found in the liver and heart. Crude protein was almost similar for liver, heart, kidney, lung but pH level was high at kidney.  Findings of this investigation of basic properties of edible and inedible by-products of Black Bengal goat will be helpful in livestock researches.Bangladesh Journal of Animal Science 52 (3): 61-68.